Counter-memory and and–and: Aesthetics and temporalities for living together. (April 2022) - Tello, Verónica
This essay traces a critical genealogy of counter-memory – spanning critical theory, film and contemporary art – bound to what Rosi Braidotti terms nomadic subjectivity. Engaging with the work of feminist and postcolonial theorists and artists, this essay charts the import of nomadic subjectivity as a method for staying with the many times and histories of global contemporaneity. It aims to move beyond thinking of counter-memory as simply a means to maintain or register erased and/or contested histories, or as a dialectical mnemonic system. It charts an alternative concept of counter-memory, one that is post-dialectical, not bound to the formulas of either/or, us/them or self/other, but which is instead committed to the endless accumulation and proximities of things – the and–and.